Antimicrobial Activity of Chrysoeriol 7 and Chochlioquinone 9, White-Backed Planthopper-Resistant Compounds, Against Rice Pathogenic Strains - Yoon-Hee Jang; Jae-Ryoung Park; Kyung-Min Kim (Biology, 2020)
As environmental damage caused by chemical pesticides appears worldwide, eco-friendly agriculture is increasing, and finding eco-friendly pesticide materials has become very important. Chrysoeriol and cochlioquinone, two flavonoids, act as an antibacterial and antioxidant, and increase the resistance of rice to the white-backed planthopper (WBPH). In this experiment, chrysoeriol 7 (C7) and cochlioquinone 9 (C9) were extracted from rice inoculated with the WBPH using MeOH, and cultivars with high extraction efficiency were selected. In addition, the antimicrobial activity of C7 and C9 against various pathogens causing disease in rice was tested. The results show that C7 has antifungal activity against Fusarium graminearum and Pythium graminicola, and C9 show antifungal activity against Cladosporium herbarum, Cladosporium cladosporioides, Gibberella zeae, Fusarium graminearum and Pythium graminicola. When both substances were treated at a concentration of 1000 ppm, they showed high inhibition rates of 62.3% and 36.2% against P.graminicola, respectively. After that, a phylogenetic tree was created to clarify the relationship between the microorganisms whose growth was inhibited and divided into three groups. This result can contribute to the study of biopesticide materials that can control pests and pathogens.